PENGARUH WADAH DAN LAMA PENYIMPANAN TERHADAP KUALITAS HASIL PENYULINGAN GETAH PINUS DARI SUMATERA BARAT - Bambang Wiyono; Poedji Hastoeti; Evi Kusmiyati (Jurnal Penelitian Hasil Hutan, 2003)
Oleoresin  of pine  (Pinus merkusii)  is a Non Wood Forest Products commodity from   West Sumatra. This oleoresin was obtained by tapping  pine  trees with square system followed  by light burning to  stimulate  more oleoresin exudate  to bleed. This research was carried out to assess the effect  of storage time and kind  of plastic laminated  container  for pine resin collected from the field with square tapped method, on rosin recovery rate and its physicochemical properties.Prior to distillation,  the pine oleoresin was kept in two kinds of containers, i.e.  plastic laminated steel  and plastic laminated  aluminium.   The distillation  of pine  oleoresin kept in plastic  laminated container produced  about  5863 % of rosin and 2026 % of turpentine  oil,  respectively. Meanwhile, the distillation products  of pine oleoresin previously  kept in plastic laminated aluminium amounted to 5663 % of rosin recovery and 2227 % of turpentine.   Analysis of variance of the experimental  results indicated that container and storage time  caused significant effect on ash content of rosin.  The ash content   of rosin  from  pine  oleoresin after  being  kept  in plastic  laminated steel  container  was somewhat lower than that  of the  one being kept in plastic laminated  steel container.  The storage time of pine oleoresin up to 6 weeks in aluminium  container could produce the rosin still comply with its prime quality and equivalent to  WW (Water White) quality  of rosin. Meanwhile, the storage time of pine  oleoresin in steel container could last only for  4 weeks to meet the requirement to produce at such  quality. The prolonged storage time of pine oleoresin caused the decrease in rosin quality. It is concluded that a plastic laminated container can be used to keep pine  oleoresin up to 6 weeks, and still rendering a prime quality rosin based on the Indonesian National Standard.